Anomalies in magnetoresistance of bismuth wires in high magnetic fields - Condrea, Elena (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2015)
Anomalous peaks in the magnetoresistance of Bi wires have been observed in a high magnetic field far above the quantum limit of the electrons. By combining a magnetic field and a uniaxial strain, we have obtained a modification of the electronic structure; as a result, the quantum limit for light and heavy electrons has changed in a different way. The origin of anomalous peaks is attributed to the complexity of the structure of the lowest Landau level of heavy electron pockets in a high magnetic field.